PENINGKATAN KEUNGGULAN BERSAING PADA BUDIDAYA PERIKANAN IKAN PATIN PADA CV. ARDYANTI PALAS - Wahyuningsih, Yusminar (Jurnal Manajemen Magister Darmajaya, 2016)
The purpose of this research were write a guidence or reference for trainers to catfish cultivation. The specific purpose were to be able to provide technical guidance, understand the definition of catfish cultivation process, raw material requirements, handling raw catfish, and conducting catfish. This reseach gave an overview of how to understand the basic theory of marketing strategy and competitive strategy to increase competitive advantage in catfish fishery cultivation (case study on CV Ardiyanti Palas) Â Key word: Catfish, Marketing Strategy, Competitive strategy, CV. Ardiyanti Palas.